Diagnostic value of standard and modified echocardiographic criteria for left ventricular noncompaction - S. N. Koretsky; E. A. Mershina; R. P. Myasnikov; O. V. Kulikova; O. V. Mirgorodskaya; A. N. Meshkov; V. E. Sinitsyn; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Aim. To assess the diagnostic value of standard and modified ultrasound criteria for left ventricular noncompaction (LVNC).Material and methods. The study included 37 patients. All patients underwent echocardiography and magnetic resonance imaging (MRI). Patients with any of the standard echocardiographic criteria for LVNC (Chin, Jenni, Stollberger) were included in the study. We studied modified echocardiographic criteria of LVNC in 4 and 3-chamber apical views in systole and diastole in the anterolateral (ALsist and ALdiast) and posterolateral (PLsist and PLdiast) walls with the non-compact to compact layer ratio (NC/C) >2. To assess the diagnostic value of the echocardiographic LVNC criteria, the specificity (SP) and sensitivity (SN), the likelihood ratio for positive (LR+) and negative (LR-) test results were calculated, and the operating characteristic curve (ROC) was analyzed.Results. The study included 19 women (51,4%) and 18 men (48,6%), aged 18 to 69 years. The mean age of the patients was 37,7±12,6 years. Relative to the Petersen's MRI-criterion for the Chin's criterion, SN was 55%, SP — 53% (LR+ =1,2, LR- =0,9); for the Jenni's criterion, SN — 55%, SP — 35% (LR+ =0,9, LR- =1,3); for the Stollberger's criterion, SN — 70%, SP — 18% (LR+ =0,9, LR- =1,7); for PLsyst criterion, SP — 82%, SN — 50% (LR+ =2,8, LR- =0,6). Relative to the Grothoff's MRI-criterion, which determined the LVNC mass as a percentage, for the Chin's criterion, SN was 69%, SP — 58% (LR+ =of 1,7, LR- =0,5); for the Jenni's criterion, SN — 85%, SP — 54% (LR+ =1,9, LR- =0,3); for the Stollberger's criterion, SN — 77%, SP — 25% (LR+ =1,0, LR- =0,9); for PLdiast criterion SP — 79%, SN — 62% (LR+ =3,0, LR- =0,5); for PLsyst criterion SP — 63%, SN — 84% (LR+ of 2,2, LR- =0,3); for ALdiast criterion, SP — 83%, SN — 69% (LR+ =4,1, LR- =0,4); for ALsyst criterion, SP — 71%, SN — 92% (LR+ =3,1, LR- =0,1). Relative to the Grothoff's MRI-criterion, which determined the LVNC mass index, for the Chin's criterion, SN was 59%, SP — 70% (LR+ =2,0, LR- =0,6); for the Jenni's criterion, SN — 67%, SP — 60% (LR+ =1,7, LR- =0,6); for the Stollberger's criterion SN — 78%, SP — 30% (LR+ =1,1, LR- =0,7); for the PLdiast criterion, SN — 33%, SP — 60% (LR+ =0,7, LR- =1,3); for PLsist criterion, SN — 59%, SP — 60% (LR+ =1,5, LR- =0,7); for ALdiast criterion, SN — 41%, SP — 80% (LR+ =2,0, LR- =0,7); for ALsist criterion, SN — 67%, SP — 90% (LR+ =6,7, LR- =0,4). Using ROC analysis with NC/C ratio of 2,3 for the ALsyst criterion, SN was 62%, SP — 92%; with NC/C ratio of 2,2 for PLsyst criteria in a posterolateral view in systole, SN — 62%, SP — 83%; with NC/C ratio of 2,1 for ALdiast criterion in an anterolateral view in diastole, SN — 54%, SP — 88%; with NC/C ratio of 2,1 for PLdiast criterion in a posterolateral view in diastole, SN — 46%, SP — 96%.Conclusion. Standard echocardiographic criteria are characterized by moderate sensitivity and low specificity. To improve the diagnostic accuracy of LVNC, the combined use of modified echocardiographic criteria is possible. As a screening of LVNC, using NC/C of 2,2 for the PLsist and NC/C of 2,3 for the PLsist to improve the specificity of the study should be useful.